Democracia participativa: ciberfeminismos contra a violência sexual e seus reflexos na biopolítica - Dieminger, Carlise Clerici (2019)
Starting from impasses and objections to the representative democracy, confronted in the current brazilian scenario, as among from the consequent necessity of the popular participation to prosper to dismiss social setbacks and oppression, such as those related to the sexual violence encountered by women, the central question persued: “could cyberfeminism contrary to sexual violence have an effect in biopolitics and assist, therefore, in the development of participatory democracy?”. It was used for these means the hypothetical-deductive method of Karl Popper, presenting as hypotesis the affirmative to the problem mentioned above, in other words, that it's indeed possible to promote more democratic participation with those activism, through the use of NTICs by citizens, foremost in the internet. It was examined, so on, if it could have beneficial repercussions in biopolitcs strategies, as regards the federal legislative arm, progressing in the manner of protection of women, specifically on sexual violence and with more attention to the legislative gap referred to lato sensu sexual harassment. In the error elimination phase, this hypotesis was tested in two different fronts: one theoretical, counterpointing auspicious studies about the subject with more skeptical ones, at the end of the second chapter; and by means of a case study, in the last chapter, in order to observe the existence or not of such reflections in biopolitics. As concerns the procedure, the historical and monographic methods were used, in association with the bibliographic, documentary and empirical techniques of research. The observation was direct and nonparticipative, having as theoretical matrix basis mainly scholars of Society in Network. As to the case study it was directed to 5 campaigns: “Fora, Cunha!”; #PrimeiroAssédio; #MeuAmigoSecreto; #PeloFimDaCulturaDeEstupro; and #CarnavalSemAssedio. Besides the already exposed, in the theorical construction of this work biopower tecnics used in biopolitics were outlined briefly, specially the Law, and its relation with sexist practices; the network society and the social movement were defined minimally, conceptualizing the genre of digital activism and cyberfeminism as a specie, while it was set among other feminist surges; the primordial goals of Feminism were identified and its history in the country was quickly brough up. At the end, the proposed conjecture rested corroborated. The manifestation “Out, Cunha!” was reflected in biopolitics by preventing the Bill of Law 5069/2013 to be voted in the plenary, threatened to the already scarce rights of sexual protection, apart from attaining the revocation of the mandate of Federal Deputy from Eduardo Cunha. The four other mobilizations studied exhibited an even greater extent in biopolitics, culminating in the creation of the Decree-Law 13718/2018.